The road back : by a liberal in opposition - Pickersgill, J. W., 1905- (Heritage., 1986)
This latest volume in Pickersgill's memoirs cover his years in opposition, from St Laurent's defeat at the hands of Diefenbaker in 1957 through to the election of a Liberal government under Lester Pearson six years later and Pickersgill's session as House Leader.